Octet-truss cellular materials for improved mechanical properties and specific energy absorption. (5th July 2019) - Song, Jian; Zhou, Wenzhao; Wang, Yuejiao; Fan, Rong; Wang, Yinchu; Chen, Junying; Lu, Yang; Li, Lixiao
Abstract: Optimization method has been widely acknowledged as an effective approach to design engineering structures, and yet few studies adopt this method to design cellular materials. Here, we firstly adopted a Kriging assisted Multi-objective Genetic Algorithm to guideline the design of octet-truss (OCT) cellular materials with the maximum specific modulus. Subsequently, additional struts were artificially introduced into the optimized OCT to further mechanically reinforce performances. All the cellular materials were precisely fabricated using a Stereolithography 3D printing technique. By reasonably optimizing the sizes of OCT, the optimized OCT with a 1.112 mm diameter and 8.282 mm cell length was achieved, which displays a superior modulus-to-mass ratio. The highest modulus and strength of as-designed cellular materials achieved 34.12 MPa and 2.64 MPa, reinforced by 3.11 and 4.81 times, respectively. Additionally, the absorbed energy efficiencies of them improved from 74.75% to 90.80%, which are significantly higher than other cellular materials. By in situ tests and fracture analyses, the high recoverability is attributed to the comprehensive effect of net-shaped architecture and elastic-plastic deformation. Graphical abstract: Unlabelled Image Highlights: Optimization design with an objective of maximum specific modulus for octet-truss cellular material was performed. In situ static and loading-unloading compressive behaviors of 3D printed cellular materials were studied. Young's moduli obtained from simulations for 3D printed cellular materials are consisted with those obtained from tests. 3D printed cellular materials are able to recover their original shapes after a compression up to 30% strain.